Analisis Kualitas Pelayanan Program Jaminan Kesehatan Nasional (JKN) di Kabupaten Jepara (Studi Pada Puskesmas Kalinyamatan dan Puskesmas Mlonggo Kabupaten Jepara) - Yoga Erlangga; Purwoko Purwoko; Puji Astuti (Journal of Politic and Government Studies, 2015)
As an inpatient health centers have facilities and medical capabilities theinitial reference point and as an organizer of a national health insurance services(JKN) or BPJS kesehatandi Jepara district, health centers and clinics MlonggoKalinyamatan required to always improve the quality of service to meet theexpectations and customer satisfaction. Effort - the government's efforts toimprove the quality of health services for the realization of a prosperous societyby organizing a national health insurance to the public in order to get properhealth care for free. However, despite no health insurance often poor and lessable to keep trouble getting the health care they deserve. This makes the need forevaluation of the quality of services of the National Health Insurance program(JKN) in health centers and community health centers Kalinyamatan Mlonggo.This study is a qualitative research. The data source for this study issecondary data such as data obtained from the results of questionnaires that willbe used as the basis of calculation of Customer Satisfaction Index (CSI). Dataanalysis was performed with Importance-Performance Analysis.Based on respondents' perceptions of service quality indicators of thehealth center Kalinyamatan, it appears that the health center patientsKalinyamatan less satisfied with the quality of service of PuskesmasKalinyamatan. Based on respondents' perceptions of service quality indicators ofthe health center Mlonggo, it appears that the health center patients Mlonggosatisfied with the quality of service of Puskesmas Mlonggo.